Dispersion of automobile industry supplier network as precondition for regional underdevelopment? (comparative study Serbia, Italy and Czech Republic) - Makojevic, Nikola; Stamenkovic, Milan; Kalinic, Ljubina (Industrija, 2017)
The aim of the paper is to analyze relationship between Fiat Automobile Industry supplier network, its geographical distribution and influence on regional development, and make comparison to similar situation in Italy and Czech Republic during automobile industry development. The industry in mentioned countries had and still have significant state support through subsides, taxes reliefs and employment programs, especially in regions defined as underdeveloped.  The research results related with Italy and Czech Republic are opposite, because state supporting programs in Czech Republic gave positive results in automobile industry development and its relation with regional development. The regions with state supporting programs developed specific economy structure which resulted in their better position within national economy. On the other hand, case of Italy and its supporting programs showed inefficiency of state in regional development because most of the regions, after auto industry closing, experienced fall in GDP, employment and exports. The results of research showed consistency with Italian results, because found out strong concentration within Sumadija region along with low level of export orientation, making such region highly dependable on Fiat automobile industry. On the other hand, within Vojvodina region, such supplier network has been developed with export oriented suppliers, included in international automobile industry value chain, making the region more flexible and more resistant on future FIAT strategic decisions.
Keywords: Underdevelopment; Supplier; Regional development; Region; Learning; Industries; Czech Republic; Czech; Automobile industry